Implementing Public Policy for Business Development: The National Entrepreneurship Development Company - Ramkissoon-Babwah, Natasha; Mc David, Jameela (Journal of Entrepreneurship, Business and Economics, 2016)
Entrepreneurship creation has been supported by many entrepreneurship development policies which have been implemented with various cross-cutting mechanisms. Such policies have been designed and executed within the international arena with mixed results in shaping the entrepreneurial growth rate. There has been limited research in the operational process of implementing public policy for stimulating entrepreneurship within developing countries and this research paper addresses this gap with an examination of the experiences of a selected public sector organization called the National Entrepreneurship Development Company Limited (NEDCO) that has the mandate for implementing the entrepreneurship policy of Trinidad and Tobago. The research has revealed that central pillars for success in public policy implementation include public sector alignment, customer responsiveness, the adoption of market orientation in operations, establishing strategic alliances within the business enterprise eco-systems, and creating monitoring and evaluation frameworks that engage a wide stake-holder net with a benchmarking and 360 degree approach. Research paper Reference to this paper should be made as follows: Ramkissoon-Babwah, N. Mc David, J. (2017). Implementing Public Policy for Business Development: The National Entrepreneurship Develop-ment Company, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 140–156.